2016
DOI: 10.1159/000442986
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of HER2 Expression in Primary Tumor and Disseminated Tumor Cells in the Bone Marrow of Breast Cancer Patients

Abstract: Objective: The aim of this study was to measure the human epidermal growth factor receptor 2 (HER2) status of disseminated tumor cells (DTCs) from bone marrow (BM) aspirates and to assess correspondence or discrepancy with the primary tumor. Methods: DTCs were isolated from the BM of 156 breast cancer patients. Cytokeratin-positive DTCs were further analyzed by the chromogenic in situ hybridization method to detect HER2 gene amplification. Results: A significant correlation (p = 0.021) was found between the HE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…We observed high discordance between ESR1 (40%) and ERRB2 (43%) status in DTCs vs. the clinical ER and HER2 status of the corresponding primary tumors, suggesting plasticity of biomarker status over the course of the disease. 61 Previous studies have also shown discordance in ER (28% 62 ; 53% 63 ) and HER2 (29–42% 64,65 ) status between DTCs and matched primary tumors. In contrast, a study using fluorescence in situ hybridization analysis showed that HER2 status in DTCs is highly concordant with that of the corresponding primary tumors.…”
Section: Discussionmentioning
confidence: 97%
“…We observed high discordance between ESR1 (40%) and ERRB2 (43%) status in DTCs vs. the clinical ER and HER2 status of the corresponding primary tumors, suggesting plasticity of biomarker status over the course of the disease. 61 Previous studies have also shown discordance in ER (28% 62 ; 53% 63 ) and HER2 (29–42% 64,65 ) status between DTCs and matched primary tumors. In contrast, a study using fluorescence in situ hybridization analysis showed that HER2 status in DTCs is highly concordant with that of the corresponding primary tumors.…”
Section: Discussionmentioning
confidence: 97%
“…Whole blood from patients and HDs was collected in 10‐mL EDTA vacutainer tubes (Becton Dickinson), and cytospins were prepared as previously described (Rack et al ., ) (for details, see Appendix S1).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, discordant expression of so-called predictive markers on the primary tumor (hormonal and growth factor receptors) and corresponding DTCs has been described. 5,9,10 Whereas therapy decisions are based solely on the expression of these markers on the primary tumor, targets in DTCs might be useful to eliminate minimal residual disease at primary diagnosis. In addition, some DTCs have been identified as cancer stem cells (CSCs) that might have the ability to renew themselves.…”
Section: Introductionmentioning
confidence: 99%